Investigations of a european network of geotechnical centrifuges on multiphase flow. Issue 1 (March 2005) - Oung, O.; Bezuijen, A.; Weststrate, F.; Haza, E.; Favraud, C.; Garnier, J.; Spiessl, S.; Taylor, N.; Coumoulos, H.; Soga, K.; Esposito, G.; Allersma, H.
Abstract : It is necessary to understand how Non-Aqueous Phase Liquids (NAPLs) migrate in the subsurface to evaluate the environmental impact of any accidental release. With this objective, five different geotechnical institutes worked together in an interactive experimental research project on two-phase flow in granular material, within the framework of the NECER programme. The main aim of the programme was to investigate the potential for using a geotechnical centrifuge in this type of research. One-dimensional and two-dimensional experiments were performed. Findings from the programme have shown that centrifuge modelling can be a useful tool in such research. It was demonstrated that less time and smaller soil samples are needed in comparison with 1g experiments and it is possible to simulate conditions at larger depth.